Investigations into the effects of scaffold microstructure on slow-release system with bioactive factors for bone repair - Pei, Baoqing; Hu, Mengyuan; Wu, Xueqing; Lu, Da; Zhang, Shijia; Zhang, Le; Wu, Shuqin (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, bone tissue engineering (BTE) has played an essential role in the repair of bone tissue defects. Although bioactive factors as one component of BTE have great potential to effectively promote cell differentiation and bone regeneration, they are usually not used alone due to their short effective half-lives, high concentrations, etc. The release rate of bioactive factors could be controlled by loading them into scaffolds, and the scaffold microstructure has been shown to significantly influence release rates of bioactive factors. Therefore, this review attempted to investigate how the scaffold microstructure affected the release rate of bioactive factors, in which the variables included pore size, pore shape and porosity. The loading nature and the releasing mechanism of bioactive factors were also summarized. The main conclusions were achieved as follows: (i) The pore shapes in the scaffold may have had no apparent effect on the release of bioactive factors but significantly affected mechanical properties of the scaffolds; (ii) The pore size of about 400 μm in the scaffold may be more conducive to controlling the release of bioactive factors to promote bone formation; (iii) The porosity of scaffolds may be positively correlated with the release rate, and the porosity of 70% to 80% may be better to control the release rate. This review indicates that a slow-release system with proper scaffold microstructure control could be a tremendous inspiration for developing new treatment strategies for bone disease. It is anticipated to eventually be developed into clinical applications to tackle treatment-related issues effectively.